A prospective evaluation of cellular bone matrix for posterolateral lumbar fusion - Dhaliwal, Joravar; Weinberg, Joshua H.; Ritchey, Nathan; Akhter, Asad; Gibbs, David; Gruber, Maxwell; Ghaith, Abdul Karim; Khalsa, Siri S.; Xu, David; Grossbach, Andrew; Viljoen, Stephanus (Clinical neurology and neurosurgery, 2025)
Autograft bone is the gold standard graft used in posterolateral lumbar intertransverse fusion (PLF) but can be limited by supply and donor site morbidity. Cadaveric cellular allografts represent an alternative source of graft material that avoids these limitations. To assess the safety and efficacy of ViviGenRCellular Bone Matrix in comparison to autograft bone in PLF. We performed a prospective study of 20 subjects who underwent PLF including 55 segmental levels. Each patient received ViviGen over the decorticated posterolateral gutter on one side an autograft bone on the other side. Fusion grading was assigned by a blinded independent neuroradiologist using a CT-based modified Lenke radiographic classification at 12 months. There was a nonsignificant increase in surgical levels showing grade A fusion for ViviGen as compared to autograft bone (62 % vs. 44 %, p = 0.056). There was a nonsignificant decrease for Vivigen compared to autograft bone in grade B (16.4 % vs 25.5 %, p = 0.241) and fusion failure (21.8 % vs 30.9 %, p = 0.279). 69 % of subjects had significant improvement in back pain numeric rating and Oswestry scores. 73 % of patients had improvement in their leg pain scores. There were no significant changes in lumbar lordosis (p = 0.611) or mean segmental lordosis (p = 0.417). At 12 months, 35 % of all levels had a > 2-degree change on flexion versus extension views while 21 % of all levels had a > 3-degree change. ViviGen cellular bone matrix demonstrates its theoretical bone-generative properties by showing non-inferiority relative to autograft with regards to fusion rates and similarity regarding patient reported outcome measures. Cellular bone matrix agents may represent a safe and noninferior alternative to autograft bone while circumventing potential drawbacks of the latter. •Cadaveric cellular allografts represent an alternative graft material that avoids autograft limitations.•Vivigen cellular bone matrix fusion rate was non-inferior to that of allograft.•Cellular bone matrix allografts may represent a safe, noninferior alternative to autograft without associated donor cite morbidity.